2019
DOI: 10.1111/acer.13966
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Social Anxiety and Alcohol and Marijuana Use Outcomes Among Concurrent Users: A Motivational Model of Substance Use

Abstract: Protective Strategies Study Team †Background: College students with more social anxiety symptoms are particularly vulnerable to problematic alcohol and marijuana use given their susceptibility for elevated anxiety symptoms in social settings combined with the normative nature of substance use. Existing research has established substance use as coping motivated for these students when examining alcohol and marijuana use problems separately. The next step is to determine whether students with more social anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 55 publications
(78 reference statements)
0
17
1
Order By: Relevance
“…Overall, risky alcohol consumption behavior has an adverse effect across psychosocial wellbeing, academic performance, quality of life, and general health [9][10][11][12][13][14]41,77,78], but also contributes to increasing the risk of drug abuse in students who already smoke cigarettes. This is of utmost importance because most adolescents and young adults believe that intermittent tobacco smoking causes little or no harm, and therefore are at more risk of engaging in risky and unhealthy behaviors [79].…”
Section: Relationship Between Tobacco Smoking Alcohol Abuse and Illegal Drug Consumptionmentioning
confidence: 99%
“…Overall, risky alcohol consumption behavior has an adverse effect across psychosocial wellbeing, academic performance, quality of life, and general health [9][10][11][12][13][14]41,77,78], but also contributes to increasing the risk of drug abuse in students who already smoke cigarettes. This is of utmost importance because most adolescents and young adults believe that intermittent tobacco smoking causes little or no harm, and therefore are at more risk of engaging in risky and unhealthy behaviors [79].…”
Section: Relationship Between Tobacco Smoking Alcohol Abuse and Illegal Drug Consumptionmentioning
confidence: 99%
“…Decreases in Expansion motives were associated with poorer treatment outcome while decreases in Coping motives were associated with better treatment outcome. In a more recent study by Villarosa-Hurlocker et al (2019), Coping motives significantly mediated the relationship between social anxiety symptoms and substance use problems. Spradlin and Cuttler (2019) also observed that Coping motives were significant mediators on the relationship between stress and frequency of cannabis use and between stress and problematic cannabis use.…”
Section: Introductionmentioning
confidence: 89%
“…Studies also reported associations with specific types of anxiety, as well as potential mediators and moderators. Generalized and social anxiety were both associated with cannabis-related problems (but not use) [50][51][52], with social anxiety also being associated with more problem severity [53] and generalized anxiety associated with use frequency (as opposed to endorsement of any use) [50,54]. Cannabis users were also more likely to endorse higher separation anxiety in adolescence compared to non-users [55].…”
Section: Primary Outcomesmentioning
confidence: 97%